Silver-incorporated poly vinylidene fluoride nanofibers for bacterial filtration. Issue 2 (1st February 2019) - Felix Swamidoss, V.; Bangaru, Mohan; Nalathambi, Gobi; Sangeetha, Dharmalingam; Selvam, Arun Karthick
Abstract: An anti-bacterial filter was developed using poly vinylidene fluoride (PVDF) nanofibers using electrospinning method blended with silver nanoparticles (AgNO3 ) of varying weight percentages of filler. Polypropylene (PP) non-woven substrate was used as base material for collecting the nanofibers. It also acted as a barrier to protect the fibers. UV-visible spectroscopy and fourier transform infra red spectroscopy confirmed the uniform dispersion of silver nanoparticles throughout the nanofibers. The experiment was designed using Box–Behnken statistical tool through three different variables namely, PP non-woven sheets (GSM), electrospinning time (hours), concentration of silver (wt%) in 15 runs. Surface morphology was analyzed using scanning electron microscopy and atomic force microscopy. Thermogravimetric analysis was performed for the analyses of mass decomposition of the material. Bacterial filtration efficiency and anti-bacterial activity studies were tested against Staphylococcus aureus and Escherichia coli for both PVDF + 0 wt% Ag fibers and PVDF-Ag nanofibers. This research shows the bacterial filtration efficiency for the prepared PVDF-Ag nanofibers as 99.86%. The prepared nanofilter was shown providing greater possibilities towards the application for clean air management. © Copyright 2019 American Association for Aerosol Research